Double pigtail stents healed acute pancreatitis resulting from afferent loop obstruction - Yue, Ping; Meng, Wenbo; Luo, Zhiwen; Bai, Bing; Li, Xun (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Yue P, Meng W, Luo Z, Bai B, Li X. Double pigtail stents healed acute pancreatitis resulting from afferent loop obstruction. Turk J Gastroenterol 2018; 29: 705-7.